Renewable Energy and Sustainable Development Nexus in Selected OECD Countries - Bozkurt, Cuma; Destek, M. Akif (International Journal of Energy Economics and Policy, 2015)
This article investigates the relationship between economic growth, renewable energy consumption, gross fixed capital and total number of labor for 1980-2012 in selected OECD countries in terms of sustainability. Four OECD countries are included in our model in order to differentiate the relationship between nuclear energy consumption and economic growth in more developed OECD countries such as the U.S. and Germany with less developed OECD countries such as Turkey and Italy. According to the results of ARDL approach, the effect of renewable energy consumption on GDP is positive in both U.S. and Germany whereas renewable energy consumption has negatively correlated with GDP in Italy and Turkey. It can be concluded that renewable energy consumption has positive effect on economic growth only in more developed countries. Keywords: Economic Growth; Sustainable Development; Renewable Energy; ARDL Bound Test. JEL Classifications: F43; Q01; Q43; Q56